2021
DOI: 10.1002/jts.22774
|View full text |Cite
|
Sign up to set email alerts
|

Addressing co‐occurring suicidal thoughts and behaviors and posttraumatic stress disorder in evidence‐based psychotherapies for adults: A systematic review

Abstract: Posttraumatic stress disorder (PTSD) is a well-established risk factor for suicidal thoughts and behaviors. Historically, guidelines for treating PTSD have recommended against the use of trauma-focused therapies with patients who are high-risk for suicide likely due to concerns about potential suicide-related iatrogenesis, specifically the "triggering" of suicidal behaviors. This systematic review examines evidence for the impact of treatments specifically designed to treat PTSD or suicide on both PTSD-and sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 85 publications
0
13
0
Order By: Relevance
“…Young people diagnosed with PTSD are more likely to report self-harm (Lim et al, 2019) or suicidal ideation (Panagioti et al, 2015). The intersection between PTSD-related distress, self-harm, and suicidal thoughts and behaviors is of particular interest; evidence-based treatments for PTSD appear to reduce suicidal thoughts and behaviors in adult populations (for a review, see Rozek et al, 2022).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Young people diagnosed with PTSD are more likely to report self-harm (Lim et al, 2019) or suicidal ideation (Panagioti et al, 2015). The intersection between PTSD-related distress, self-harm, and suicidal thoughts and behaviors is of particular interest; evidence-based treatments for PTSD appear to reduce suicidal thoughts and behaviors in adult populations (for a review, see Rozek et al, 2022).…”
mentioning
confidence: 99%
“…The goal of TF-CBT is to decrease distress via gradual exposure by building alternative skills for coping with distress by promoting exposure to and enhancing tolerance of affective states that might otherwise precipitate self-harm, suicidal ideation or behavior (see Rozek et al, 2022 for review, see Smith et al, 2014). Whereas it is accepted that temporary elevations in distress may occur during treatment, these TF-CBT components may minimize distress and potentially reduce risky behaviors.…”
mentioning
confidence: 99%
“…Research in this area would also benefit from investigations of the role of specific PTSD symptom constellations associated with suicidal behavior, and the extent to which other psychosocial factors such as impulsivity, or shame, may augment or mediate this risk. PTSD treatments such as cognitive processing therapy or prolonged exposure have been shown to reduce both PTSD‐ and suicide‐related outcomes (Rozek et al, 2021). Suicide‐focused treatments (e.g., cognitive therapies for suicide prevention) also reduced suicide‐related outcomes, but the findings were mixed for their impact on PTSD‐related outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of co‐occurring conditions, such as PTSD, following established best practices is recommended for individuals with an intermediate‐to‐low risk. The findings from a recent systematic review demonstrated that PTSD treatments, most frequently CPT and PE, and treatment plans that combined PTSD treatment with suicide‐focused treatments reduced both PTSD symptoms and suicidality, whereas suicide‐focused treatments alone had beneficial effects on suicidality but led to less change in PTSD symptoms (Rozek et al., 2021).…”
Section: Frequently Asked Questions About the Cpgmentioning
confidence: 99%